Consumer perceptions of free-range laying hen welfare. Issue 8 (1st August 2016) - Pettersson, Isabelle Claire; Weeks, Claire Alexandra; Wilson, Lorna Rachel Maven; Nicol, Christine Janet
Abstract : Purpose: To understand which factors and resources free-range egg consumers believe are important for hen welfare. Design/methodology/approach: An online survey was distributed via the mailing list of a UK free-range egg brand receiving 6, 378 responses. The survey was mostly five-point Likert-scale based. The same survey was also distributed to a group of animal welfare specialists receiving 34 responses. Findings: Findings Respondents bought free-range eggs because hens are 'happier' (74.2%) and 'healthier' (69.0%) and because they believed such eggs to taste better (57.9%). They rated all the suggested factors that might contribute to hen welfare as 'important' or 'very important' (on average) but believed outside access and fresh air to be most important. Respondents rated the suitability of resources relating to behavioural needs high ('suitable' or 'very suitable') indoors and shelter as the most suitable outdoors. Consumers differed from welfare specialists in their views on factors contributing to hen welfare, but their views on resource suitability were similar. Research limitations/implications: The sample was biased towards free-range egg consumers who had expressed an interest in a brand marketed as high welfare. Originality/value: This is the first study to ask consumers what they consider to be important for hen welfare and how they think hen welfare can be improved. Because consumers can affect on-farm welfare through their purchasing habits assessing the degree of agreement between consumers and animal welfare specialists is important.